Ferroptosis: a new regulatory mechanism in neuropathic pain - Li, Lu; Guo, Lingling; Gao, Rui; Yao, Mengwen; Qu, Xinyu; Sun, Guangwei; Fu, Qi; Hu, Cuntao; Han, Guang (Frontiers in Aging Neuroscience, 2023)
Neuropathic pain (NP) is pain caused by damage to the somatosensory system. It is a common progressive neurodegenerative disease that usually presents with clinical features such as spontaneous pain, touch-evoked pain, nociceptive hyperalgesia, and sensory abnormalities. Due to the complexity of the mechanism, NP often persists. In addition to the traditionally recognized mechanisms of peripheral nerve damage and central sensitization, excessive iron accumulation, oxidative stress, neuronal inflammation, and lipid peroxidation damage are distinctive features of NP in pathophysiology. However, the mechanisms linking these pathological features to NP are not fully understood. The complexity of the pathogenesis of NP greatly limits the development of therapeutic approaches for NP. Ferroptosis is a novel form of cell death discovered in recent years, in which cell death is usually accompanied by massive iron accumulation and lipid peroxidation. Ferroptosis-inducing factors can affect glutathione peroxidase directly or indirectly through different pathways, leading to decreased antioxidant capacity and accumulation of lipid reactive oxygen species (ROS) in cells, ultimately leading to oxidative cell death. It has been shown that ferroptosis is closely related to the pathophysiological process of many neurological disorders such as NP. Possible mechanisms involved are changes in intracellular iron ion levels, alteration of glutamate excitability, and the onset of oxidative stress. However, the functional changes and specific molecular mechanisms of ferroptosis during this process still need to be further explored. How to intervene in the development of NP by regulating cellular ferroptosis has become a hot issue in etiological research and treatment. In this review, we systematically summarize the recent progress of ferroptosis research in NP, to provide a reference for further understanding of its pathogenesis and propose new targets for treatment.